2022
DOI: 10.1371/journal.pone.0263069
|View full text |Cite
|
Sign up to set email alerts
|

Pre-infection 25-hydroxyvitamin D3 levels and association with severity of COVID-19 illness

Abstract: Objective Studies have demonstrated a potential correlation between low vitamin D status and both an increased risk of infection with SARS-CoV-2 and poorer clinical outcomes. This retrospective study examines if, and to what degree, a relationship exists between pre-infection serum 25-hydroxyvitamin D (25(OH)D) level and disease severity and mortality due to SARS-CoV-2. Participants The records of individuals admitted between April 7th, 2020 and February 4th, 2021 to the Galilee Medical Center (GMC) in Nahar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
54
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 43 publications
2
54
0
1
Order By: Relevance
“…The benefit of vitamin D supplements in preventing acute respiratory tract infections was observed via a meta-analysis of 11,321 participants and other reviews [23][24][25][26][27]. The possibility of decreasing the risk of respiratory tract infections, including coronavirus disease 2019 (COVID-19), may contribute to several immune pathways, such as stimulating antiviral mechanisms, reducing proinflammatory cytokines, modulating concentrations of ACE2, and decreasing the chances of endothelial dysfunction [28].…”
Section: Introductionmentioning
confidence: 99%
“…The benefit of vitamin D supplements in preventing acute respiratory tract infections was observed via a meta-analysis of 11,321 participants and other reviews [23][24][25][26][27]. The possibility of decreasing the risk of respiratory tract infections, including coronavirus disease 2019 (COVID-19), may contribute to several immune pathways, such as stimulating antiviral mechanisms, reducing proinflammatory cytokines, modulating concentrations of ACE2, and decreasing the chances of endothelial dysfunction [28].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was discovered that VDR polymorphisms are independently related to the severity of COVID-19 and patient survival (Apaydin et al, 2022). In addition, recent Israeli research based on the rst two pandemic waves, which was prior to vaccine usage, discovered a risk of having severe COVID-19 in vitamin D de cient individuals (Dror et al, 2022). This case-control study is one of the few studies evaluating the association between SARS-CoV-2 variants of concern and VDR gene variations.…”
Section: Discussionmentioning
confidence: 87%
“…The reduction in the vitamin D levels with age and the seasonal variation, with the lowest values during the cold season, seems to be in relation to higher case-fatality rates in older patients [ 15 ] and similarly with an increased seasonal incidence of the viral pathology. In a recent study, Dror et al found that hypovitaminosis D before SARS-CoV-2 infection was associated with more severe/critical illness, compared to patients with moderate/mild form, and the mortality rate was higher among patients with vitamin D insufficiency [ 38 ]. Similar to the previously mentioned study, we found that vitamin D deficiency is prevalent in moderate/severe disease forms and advanced age, compared to mild disease forms and younger subjects.…”
Section: Discussionmentioning
confidence: 99%